Crown−rump length discordance in the first trimester: a predictor of adverse outcome in twin pregnancies?. (12th February 2014) - Johansen, M. L.; Oldenburg, A.; Rosthøj, S.; Maxild, J. Cohn; Rode, L.; Tabor, A.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2014; 43: 246–246